Familial hypophosphatemic rickets: report of a case - Edi S Tehuteru; Taralan Tambunan (Paediatrica Indonesiana, 2003)
Familial Hypophosphatemic Rickets (FHR) wasfound for the first time by Albright in 1937 andis also called vitamin D resistant rickets. 1-3 It isa disease that can occur through x-linked dominant,autosom dominant, and sporadic inheritance. 1-4Albright found that most FHR is x-linked dominanttype. 3 To distinguish between x-linked dominant andautosom dominant, the family pedigree can not beused, because it may look alike. Usually this diseasecan be distinguished genetically. The gene that isresponsible for x-linked dominant is located in Xp21while for autosom dominant is in 12p13. 4 Sporadictype can easily be distinguished from the other two.In the family pedigree, there is no other FHR patientbesides the patient himself. 3,4 The case that we areabout to report was a sporadic type FHR.